EVALUATION OF LIGHT SHELF DESIGN PERFORMANCES TO THE DAYLIGHT’S SUNLIGHT PENETRATION ON SINAR MAS LAND PLAZA BUILDING TANGERANG TO INCREASE THE GREEN MARK ASSESSMENT - Monica Elizabeth ; Ryani Gunawan (Riset Arsitektur (RISA), 2018)
Abstract- Light shelf is one of the daylighting strategies used in Sinar Mas Land Plaza Tangerang. However, based on observations made on the object of research, light shelf design on Sinar Mas Land Plaza Tangerang is not optimal. This is because the purpose of a light shelf that should reflect sunlight directly to enter much deeper into the room does not occur. This is evident in the use of artificial lighting in areas close to openings, so it is necessary to evaluate the light shelf design to improve light shelf performance, which is also useful for improving the Green Mark BCA assessment.This research uses experimental research method to see daylight penetration by simulating model using Ecotect which can simulate model by ray simulation. Evaluation is done by manipulating variables from light shelf design such as ceiling design aspect, light shelf shape, and light shelf slope to see effective light shelf design to be applied to Sinar Mas Land Plaza Tangerang. Based on the research, it can be concluded that the performance of the existing light shelf design is not optimal because of the fins that are above the light shelf to block out direct sunlight. The sloped ceiling design also affects the daylight penetration distance into space. Light shelf design that effective at North orientation is a light shelf design with curved shapes, while the light shelf design that effective at South orientation is a light shelf design with a slope of 200. Improving the light shelf design can increase the Green Mark rating up to 8 points. Key Words: light shelf, daylight penetration, assessment of Green Mark, Ecotect